ANALYSIS OF LEARNING STYLE AS A MEDIATOR OF THE INFLUENCE OF LOGICAL INTELLIGENCE AND INTERACTIVE MEDIA ON MATHEMATICS RESULTS - Oktafiana, Riska; Daryono, Rihab Wit (Abjadia : International Journal of Education, 2024)
Learning style is very important as a link between the development of logical intelligence and the effectiveness of interactive media in improving mathematics learning outcomes. By paying attention to students' learning preferences, the use of interactive media can be optimized to strengthen their logical skills and improve their achievement in mathematics. This research aims to analyze the role of learning style as a mediator in the influence of logical intelligence and the use of interactive media on mathematics learning outcomes. This research method is a survey method with a quantitative approach. The number of samples taken was 65 class IV students from MI Kresna. Data was collected through a questionnaire with a Likert scale and analyzed using descriptive statistical techniques and regression analysis to test hypotheses. PLS-SEM analysis is used to analyze data and test and evaluate the construction of problem capability measurement variables. The results of the research show that logical intelligence on learning style (β=0.550 ; ρ =0.000) and learning style on mathematics results (β=0.179 ; ρ =0.740) have an insignificant effect, apart from that learning style is proven to mediate the influence of interactive media (β=0.052 ; ρ=0.424) and logical intelligence (β=0.099; ρ=0.517) on mathematical results. The implication of this research is the importance of logical intelligence and interactive media in improving fourth grade students' mathematics results. Recommendations for this research include providing training that focuses on teacher awareness and motivation in using interactive media effectively. Thus, this research is expected to significantly improve logical intelligence, interactive media, and ultimately student mathematics results.